Tools, trails and time: Debating Acheulian group size at Attirampakkam, India. Issue 130 (May 2019) - Pappu, Shanti; Akhilesh, Kumar
Abstract: Estimating Acheulian group sizes based on a fragmentary archaeological record is fraught with difficulties, more so in regions like India, where lithics form the primary source of information. Here, we review current approaches towards modeling group size in Indian archaeology. We then examine to what extent one may address issues related to seasonality, fission-fusion strategies and group size in the context of Acheulian sites, drawing on our research along the southeastern coast of India. We move between multiple scales of analysis: from the regional Acheulian archaeological record to specific studies at the site of Attirampakkam (ATM). We consider aspects of site distribution, sizes, artefact densities and Acheulian lithic reduction strategies, factoring in issues related to geomorphology, taphonomy and chronology. Acheulian hominins occupied the study region over the early to middle Pleistocene, and the fragmented lithic reduction sequence noted on landscape scales suggests diverse site functions structured by ease of access to quartzite raw material for large flake production in addition to other resources. In contrast to most sites, the absence of raw material at ATM necessitated groups to anticipate this, and organize their behavior on landscape scales, and on-site, to resolve this issue. We show how successive groups were attracted to the site over the early Pleistocene, potentially aiming at exploiting seasonally predictable biological resources in a riparian environment, knowledge of which was transmitted across generations. Considerations of the spatial and temporal variability in artefact densities across a vast site area, along with aspects of the lithic reduction sequences suggests a short-duration occupation by a potentially large group, possibly resulting from aggregation of several small groups as noted in some ethnographic examples of hunter-gatherer fission-fusion strategies. We show drastic changes in behavioral organization in the succeeding Middle Palaeolithic phases at the site and in the region.